Vapor Phase Electrochemistry 2: Spherical and Spheroidal Air Plasmas - Turner, David (Journal of Scientific Exploration, 2024)
Among the rare meteorological phenomena that exist are long-lived spheroidal air plasmas. Of these, lightning balls are best characterized. Closely related are earth-lights, tornadic lights and Unpredictable Flying Objects (UFOs). Early physicists took all such phenomena to be plasmas and would refer to them as electric fire or fireballs. Many physicists today do not accept that these light emitting objects are plasmas because they neglect a variety of influences that result from chemical change. Stability results mainly from entropy production as an ionized, metastable form of nitrous acid, produced at an air plasma surface, refrigerates the surface through its conversion to the stable acid. It is then oxidized to nitric acid in an aerosol form, which restricts the inflow of air to the plasma surface. This can explain the “ surface tension” of lightning balls early, as hypothesized by Stakhanov (1979). Studies of earth-lights (Teodorani, 2004) imply that these are plasma balls held together by the same forces as those providing mechanical stability to lightning balls. Studies of flame balls in space support this view. UFOs and earth-lights are structured similarly but the plasma components of UFOs can be held together by far stronger forces. Potentially, air plasmas have important technological implications since they are all powered by extracting and using chemical energy from the air. Crucially, this energy can only be extracted from air whose temperature is below 150 C. If air plasmas could be prepared artificially, they would prove invaluable in supplying ample carbon-free electrical energy.